Evaluating The Effectiveness Of School-Based Management In Enhancing Educational Quality: A Case Study Of Smp Negeri 3 Manado - Imelda Kakomole; Shelty Deity Meity Sumual; Jeanne Miera Mangangantung (International Journal of Science and Environment (IJSE), 2025)
This research analyzes the effectiveness of implementing School-Based Management (SBM) in improving educational quality at SMP Negeri 3 Manado. The main objectives were to analyze SBM's effectiveness, identify supporting and inhibiting factors, describe the school's efforts to overcome obstacles, and evaluate its contribution to academic and non-academic quality. Employing a descriptive qualitative approach, data was collected through interviews, observations, and documentation. The findings indicate that SBM is effective in enhancing educational quality through active participation from all school community members in program planning, implementation, and evaluation. This positively impacts learning quality (more innovative teachers, active students) and improves teacher professionalism. Data-driven accountability is also key to its effectiveness. Supporting factors include teacher commitment, team cohesion, and the principal's open leadership. However, challenges include uneven human resource capacity and sub-optimal utilization of facilities. The school addresses these by conducting regular program evaluations, actively involving all school elements, and fostering a culture of discussion. SBM's contribution is evident in improved academic quality (learning processes) and non-academic aspects (environment, extracurriculars, collaboration). This study concludes that SBM plays a vital role in educational quality improvement, yet requires adaptive strategies for HR development and resource optimization.